Analysis of drift orbits in closed magnetic configurations with drift rotation transformation - Khvesyuk, V.I.; Chirkov, A.Yu. (Вопросы атомной науки и техники, 2002)
A study is made of the dynamics of particles interacting with electromagnetic field fluctuations in a plasma in the presence of a magnetic field. Possible mechanism of anomalous transport is analyzed. Estimates of the diffusion coefficient are proposed based on the calculations of particle trajectories.